TEACHING SELF-EFFICACY BELIEFS, SKILLS AND PERCEPTIONS OF PRE-SERVICE SCIENCE TEACHERS - Yıldız, Emre; Urun Arici, Nesrin (International Online Journal of Education and Teaching, 2021)
In this study, it was aimed to examine the teaching self-efficacy beliefs, skills, and perceptions of pre-service science teachers. The case study, one of the qualitative designs, was used in the study. The participant group of the study consists of 4 pre-service science teachers studying in the last year of a university in the 2018-2019 academic year. Teacher self-efficacy scale, observation and interview were used as data collection tools. Regression analysis and content analysis methods were used in data analysis. It was determined that many of the teaching skills of the pre-service teachers remained below the medium level and their skill levels were generally acceptable and intermediate, and between intermediate and good levels. It was determined that pre-service teachers had wrong behaviors such as not ensuring student participation, not being able to attract students’ attention, activities not being appropriate for the student level, not being able to concretize abstract concepts, not evaluating the level of achieving the target gains, and not being able to achieve class dominance. As a result, although pre-service teachers have high self-efficacy beliefs about teaching, their teaching skills are at medium level and they have deficiencies in the teaching process and planning teaching.